THE UTILIZATION OF GOVERNMENT FINANCIAL STATEMENTS BY EXECUTIVES: THE CASE OF LOCAL GOVERNMENTS IN INDONESIA - Nurkholis, Nurkholis; Affandi, Arlisya Tika (Accounting Department,, 2019)
The objective of this study is to explore the utilization of LKPD produced through the implementation of accrual accounting. Using the cases of three local governments in Indonesia, it is revealed that the implementation of accrual accounting is still superficial. As predicted, financial statements that are frequently used by executive’s and local goverment are Budget Realization Statements and balance sheet. Other reports have been produced only to comply with government regulations, but they are not actually used. The implication of this study is that there is a need to improve executive’s understanding about accrual accounting, so that the objective of financial reporting as stipulated in Government Regulation No. 71 of 2010 can be achieved.